Study of Cephalic Index in medical students of West Bengal - Bhanarkar, Ujwala; Koley , Baishakhi (Journal of Indian Academy of Forensic Medicine, 2020)
Human beings are always very much interested in making comparison over other creatures to prove their superiority. Different types of measurements are important tool for comparative study, related to various characteristic features. Craniofacial measurement especially cephalic index is an important tool among those comparative studies, useful in determining different head and face shapes. Present study is going to be carried out with an objective to find out Cephalic Index of Medical Students of West Bengal. Total 325 young and healthy medical students were taken as subjects, whose head length, head breadth were measured. Cephalic indices of the subjects were calculated by Hrdlicka’s method. Most of the subjects were found mesocephalic, 59 % male & 51.7 % female. Mean cephalic index in male 78.45 % ± 2.44 and for female 77.65 % ± 3.58. Mean cephalic index irrespective of gender was found 80.5 % ± 3.67. This study showed the head type of students in West Bengal was mesocephalic predominant. This statistically significant data can be utilized by anthropologist or forensic expert.